Verbal Self‐Monitoring in the Second Language. (September 2016) - Broos, Wouter P. J.; Duyck, Wouter; Hartsuiker, Robert J.
Abstract : Speakers monitor their own speech for errors. To do so, they may rely on perception of their own speech (external monitoring) but also on an internal speech representation (internal monitoring). While there are detailed accounts of monitoring in first language (L1) processing, it is not clear if and how monitoring is different in a second language (L2). Here, we ask whether L1 and L2 monitoring differ and, if so, where the differences lie. L1 and L2 might differ in the speed with which monitoring is performed but also in their monitoring foci. We discuss studies on bilingual language control and suggest that self‐monitoring might function as a last‐resort control process. We conclude with speculation on the role self‐monitoring might play in L2 learning and suggestions for future research.